(untitled) - Teye, Prof. G. A. (UDS International Journal of Development, 2021)
The UDS International Journal of Development (UDSIJD) is out with the second issue for 2020 (Vol. 7,Issue 2). Due to some technical challenges, this second issue has been a bit late.The journal acknowledges that despite the challenges faced due to the Covid-19 pandemic, authors,reviewers and the editorial team have worked tirelessly to make this issue a success and therefore, deservemuch commendation.A total of ten papers are included in this second issue. Four papers cover Applied Sciences whilst six arein the Humanities.The UDSIJD continues to encourage young academics, researchers, development practitioners andentrepreneurs to submit manuscripts of empirical research findings, policy analysis and topical issuesfrom varied disciplines with a development focus, on a regular and sustained basis.The Editorial Team wishes to sincerely thank the University Management, authors, reviewers and staffof the Journal and all those who in diverse ways have supported in making this issue of the journal areality.The Editor-in-ChiefProf. G. A. Teye